Third-high Level Dialogue on gender and climate change In Nigeria - Enemali, Theophilus; Awinoh, Martha; Lecoutere, Els (CGIAR System Organization, 2024)
The third high-level dialogue held in Abuja, Nigeria, on October 9, 2024, came at a crucial time, marking a significant step in addressing the gender equality and climate resilience challenges within Nigeria’s agrifood systems. This dialogue provided a platform for gender and climate experts to engage in constructive discussions about the persistent barriers women face in agriculture, exacerbated by climate change and entrenched gender norms. It sought to identify collaborative actionable solutions that address gender inequalities in Nigeria’s agrifood systems, particularly around the unequal access to resources, decision-making power, and technologies that women face among others. The discussions joined by stakeholders from government, civil society, research institutions and private sector was guided by two themes: the first theme focused on positive gender norms and socio-technical innovation bundles; the second theme on voice, inclusive governance and social protection for equitable agrifood systems in a climate crisis.